2019
DOI: 10.1097/mjt.0000000000000825
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Pulmonary Embolism Presenting as Syncope

Abstract: Background: Syncope represents a common condition among the general population. It is also a frequent complaint of patients in the emergency department (ED). Pulmonary embolism (PE) considers a differential diagnosis, particularly in a case of syncope without chest pain. Study Question: What is the prevalence of PE among patients who presented an episode of syncope to the ED and among those hospitalized for syncope in a tertiary care hospital? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Our study has demonstrated that the prevalence of PE is low in patients presenting with syncope using a large nationwide database compared to the recently published report [5] and similar to other studies [13,14]. Our study also showed that a majority of patients had at least one syncope associated diagnosis at index admission, and one should consider PE as an etiology if syncope is unexplained [15]. More recently, Costantino et al have shown a similar low prevalence rate of PE of less than 3% in hospitalized patients and less than 1% within 90 days of follow-up [16].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study has demonstrated that the prevalence of PE is low in patients presenting with syncope using a large nationwide database compared to the recently published report [5] and similar to other studies [13,14]. Our study also showed that a majority of patients had at least one syncope associated diagnosis at index admission, and one should consider PE as an etiology if syncope is unexplained [15]. More recently, Costantino et al have shown a similar low prevalence rate of PE of less than 3% in hospitalized patients and less than 1% within 90 days of follow-up [16].…”
Section: Discussionsupporting
confidence: 89%
“…These results warrant a prospective investigation regarding relevant workup for PE in patients admitted for syncope, which might include using pretest probability score like PERC Rule or Wells Criteria, appropriate use of D-dimer testing and considering further imaging based on the results [19][20][21]. It might be more reasonable to consider VTE work up in syncope patients with hemodynamic instability [15,22].…”
Section: Discussionmentioning
confidence: 97%
“…However, perfusion or ventilation abnormalities caused by hypoxemia might be significantly involved in the development of syncopes. Due to transient depressions in cardiac output, main pulmonary or lobar artery obstructions can also be associated with syncope [ 22 , 23 ]. In intermediate-risk PE patients with right ventricular involvement, the presence of syncopes is associated with a more complicated in-hospital course [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Syncope in PE patients may be caused by cerebral hypoperfusion due to reduced cardiac output, arrhythmias due to hemodynamic instability, or neurogenic syncope (Keller et al, 2018;Siddappa Malleshappa et al, 2020). Inadequate oxygen supply due to hypoxemia is also a cause of syncope (Keller et al, 2018;Pop et al, 2019). In the emergency department, 2.2% of syncope patients were eventually diagnosed with PE (deSouza, 2020).…”
Section: Discussionmentioning
confidence: 99%